“Reason” of political and religious moderation in the book of Ghiyāth al-Umam by al-Juwaynī and its contemporary Southeast Asian context - Mohammad Syifa Amin Widigdo; Awang Azman Awang Pawi (Cogent Arts & Humanities, 2023)
This article presents a critical reading of the work of Imam al-Haramayn al-Juwayni (d. 1085) entitled Ghiyath al-Umam (Ghiyāthī). This reading is necessary to fill in the gaps in the study of the roots and precedents of moderation in the work of Islamic political thought in the medieval period. Al-Juwayni’s political and religious thoughts, when faced with non-ideal political and religious situations, showed a well-founded character of moderation. The solutions to the problems of his time that he offered were the products of “moderation reason” rooted in his religious beliefs and political pragmatism. The precedent of “moderation reason” shown by al-Juwayni finds its contemporary relevance in the model of the attitude of Nahdlatul Ulama (NU) and Muhammadiyah towards Pancasila in the Unitary State of the Republic of Indonesia. They formulated the concept of political and religious thought in accordance with the context of al-Juwayni’s intellectual, political, and religious attitudes. In the end, this paper indicates that the concept of moderation is not a modern discourse programmed by the government without having roots and precedents in Islamic political thought.